Using Open-Data Portals, Remote Sensing and Computational Modelling to Investigate Historic Wreck Sites and Their Environments: 45 Years on from Muckelroy - Gregory, David (The international journal of nautical archaeology, 2025)
We explored site formation processes at 549 shipwrecks in the North and Baltic Seas using multibeam echosounder (MBES) data and environmental/anthropogenic variables. Phase 1 classified the structural integrity of each wreck. Phase 2 used regression modelling to explore correlations between wreck class and environmental variables at individual sites. A best-fit model comprised depth, salinity, fishing intensity, and wreck year. In phase 3 multi-criteria analysis predicted preservation potential across the full model domain. Highest preservation potential is modelled for the southern Baltic Sea and Norwegian Trench, with low potential in shallower areas of the North Sea and off England, Netherlands and Germany.